PEMANFAATAN BUKU SEKOLAH ELEKTRONIK (BSE) MELALUI SMARTPHONE PADA MATA PELAJARAN IPS TERPADU DI SMP NEGERI 1 EREMERASA - Irpan Ansyari (Jurnal Pendidikan Sang Surya, 2021)
Abstract: This class action research has the aim of studying the application of the use of electronic school books as a source of learning as well as efforts to improve student achievement. As for the background of this research because e-books or electronic school books are one of the interactive media along with other advantages such as easy, practical and anti-damaged. This research data collection technique by providing formative tests on each cycle and observation sheet. The data analysis method is quantitative descriptive. Learning achievement is analyzed by comparing tests between cycles. Indicators of learning achievement success in the form of mastery learning classically Greater Equal Than 85 percent. The results showed an increase in mastery learning from 75 percent or 15 people who finished in cycle I, to 90 percent  or 18 people who completed in cycle II. This proves that the use of BSE on smartphones as a source of learning can improve mastery and learning achievement. The conclusion of this study is the effective use of BSE through smartphones can improve student achievement in class IX B in SMP Negeri 1 Eremerasa. Research recommendations to teachers to make maximum use of learning resources in schools such as BSE. And to students to better utilize the use of smartphones to increase knowledge and knowledge.